ANALISIS KELENGKAPAN PENULISAN DIAGNOSA TERHADAP KETEPATAN PEMBERIAN KODE CEDERA DAN KODE EXTERNAL CAUSE PADA KASUS KECELAKAAN DI RUMAH SAKIT UMUM UNIVERSITAS MUHAMMADIYAH MALANG - Ashila Irka Faza; Chyntia Vicky Alvionita (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2023)
In the implementation of coding in the case of accidents at the General Hospital of the University of Muhammadiyah Malang there are still inaccuracies in coding of 79.2% and accuracy of 20.8%. The purpose of this study was to analyze how the completeness of the diagnosis relates to the accuracy of coding injuries and codesexternal cause in case of an accident. The research method used is an analytical survey approachCross Sectional. To determine the relationship between the completeness of writing a diagnosis on the accuracy of coding injuries and codesexternal cause In the case of an accident, a statistical test was carried out with the testWho Squareusing the IBM SPSS application version 25. Using the saturated sampling technique, a total sample of 77 accident cases was obtained in the 2022-2023 period. In this study, the results of the diagnosis accuracy were 20.8% and 79.2% inaccuracy. This inaccuracy is caused because the officer did not do the coding for the codeexternal cause. Based on the SPSS results, it was found that there was a relationship between the completeness of writing a diagnosis and the accuracy of coded injury and external cause codes in accident cases at the General Hospital of the University of Muhammadiyah Malang. These results are due to the writing of the diagnosis which still does not include the chronology of the accident. This can cause coding errors by coding officers at the hospital.